Identification of hub genes related to DNA damage response in asthma via combinative bioinformatics strategy - Li He; Fangmei Lin; Yawen Zhou; Meihua Dong; Mingfang Deng; Jing Li; Nan Jia (Journal of International Medical Research)
Objective Emerging evidence has indicated the potential role of DNA damage response in asthma pathogenesis, but the underlying mechanisms remain elusive. Therefore, this study aimed to identify key diagnostic DNA damage response–related genes in asthma and explore their regulatory networks. Methods Differentially expressed genes between healthy individuals and patients with asthma were identified using the Gene Expression Omnibus database. Hub DNA damage response–related differentially expressed genes were determined via protein–protein interaction network and verified through gene expression analysis. Receiver operating characteristic curve was employed to identify diagnostic genes. Transcription factor–microRNA–target gene interactions were analyzed to uncover the regulatory networks in asthma pathogenesis. In this observational study, reverse transcription quantitative polymerase chain reaction was used to validate gene expression levels in healthy individuals and patients with asthma. Results Six of the nine hub genes ( ATM , PCNA , CUL4A , PARP2 , HLTF , and NBN ) were identified as key diagnostic genes. These genes may contribute to asthma progression by regulating inflammatory pathways, such as cyclic GMP–AMP synthase–stimulator of interferon genes, senescence-associated secretory phenotype, autophagy, and apoptosis. Three microRNAs and eleven transcription factors were recognized as potential regulators. Reverse transcription quantitative polymerase chain reaction confirmed the downregulation of DNA damage response genes in asthma and revealed distinct expression patterns across different asthma endotypes. Conclusion Six DNA damage response–related genes may serve as diagnostic biomarkers for asthma, and the transcription factor–microRNA–DNA damage response gene network highlights the role of DNA damage response in asthmatic inflammation.